বঙ্গবন্ধু শেখ মুজিবকে ঘিরে কিছু ঘটনা ও বাংলাদেশ - মিয়া, এম.এ. ওয়াজেদ 1942-2009. (ঢাকা : ইউনিভার্সিটি প্রেস, 1993)
Reminiscences of the major political events in Bangladesh, 1961-1992; includes contributions of Sheikh Mujibur Rahman, 1922-1975, former president.
In Bengali.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা [৪৫১]-৪৫৩) অন্তর্ভুক্ত।
Donated By Akbar Ali Khan (38495)
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975.; Bangladesh -- Politics and government; Bangladesh -- Politics and government -- 1971-